OSM-11 facilitates LIN-12 Notch signaling during Caenorhabditis elegans vulval development. - Hidetoshi Komatsu; Michael Y Chao; Jonah Larkins-Ford; Mark E Corkins; Gerard A Somers; Tim Tucey; Heather M Dionne; Jamie Q White; Khursheed Wani; Mike Boxem; Anne C Hart (PLoS Biology)
Notch signaling is critical for cell fate decisions during development. Caenorhabditis elegans and vertebrate Notch ligands are more diverse than classical Drosophila Notch ligands, suggesting possible functional complexities. Here, we describe a developmental role in Notch signaling for OSM-11, which has been previously implicated in defecation and osmotic resistance in C. elegans. We find that complete loss of OSM-11 causes defects in vulval precursor cell (VPC) fate specification during vulval development consistent with decreased Notch signaling. OSM-11 is a secreted, diffusible protein that, like previously described C. elegans Delta, Serrate, and LAG-2 (DSL) ligands, can interact with the lineage defective-12 (LIN-12) Notch receptor extracellular domain. Additionally, OSM-11 and similar C. elegans proteins share a common motif with Notch ligands from other species in a sequence defined here as the Delta and OSM-11 (DOS) motif. osm-11 loss-of-function defects in vulval development are exacerbated by loss of other DOS-motif genes or by loss of the Notch ligand DSL-1, suggesting that DOS-motif and DSL proteins act together to activate Notch signaling in vivo. The mammalian DOS-motif protein Deltalike1 (DLK1) can substitute for OSM-11 in C. elegans development, suggesting that DOS-motif function is conserved across species. We hypothesize that C. elegans OSM-11 and homologous proteins act as coactivators for Notch receptors, allowing precise regulation of Notch receptor signaling in developmental programs in both vertebrates and invertebrates.